Tree cavity density is a limiting factor for a secondary cavity nester in second-growth Andean temperate rainforests - Altamirano, Tomas A.; Novoa, Fernando; Ibarra, Jose Tomas; Navarrete, Sergio A.; Bonacic, Cristian; Martin, Kathy (My University, 2024)
Cavity-nesting bird populations are most frequently limited by the number of tree cavities available in second-growth forests. However, this possible limitation of a key resource is less clear in old-growth forests. We compared forest attributes (i.e., basal area, density of larger trees, density of dead trees, and tree cavity density) in second-growth and old-growth stands in Andean temperate rainforests in southern Chile. To examine the role of nest-site availability in limiting the populations of Aphrastura spinicauda (Thorn-Tailed Rayadito), we monitored their populations in both forest types during a 5-year period (2008-2013), while we conducted an experiment in which nest boxes were added and then, after two years, removed by blocking cavity entrances. In old-growth forests, as compared to second-growth forests, we found a more than double basal area (99.6 vs. 43.7 m2 ha-1), a 3 times higher density of larger trees (88.2 vs. 36.4 trees ha-1), and a 1.5 times higher number of small cavities (25.9 vs. 10.3 cavities ha-1). The density of cavities also strongly increased with tree diameter and basal area. In second-growth forests, A. spinicauda showed a strong response to the addition, and later to the removal of nest boxes, with population abundance increasing by 13% and then decreasing by 50%, respectively. In contrast, we found no impact on old-growth stands. Our experiment emphasizes the importance of maintaining large and dead trees in second-growth, disturbed, and managed forests. These trees provide suitable cavities for A. spinicauda, and likely many other secondary cavity nesters, increasing their abundance in a Globally significant Biodiversity Hotspot in southern South America. A Spanish translation of this manuscript is available as Supplementary Material. center dot Cavity availability is considered a limiting factor, potentially regulating the breeding population density of avian cavity nesters.center dot We compared forest attributes in second-growth and old-growth stands and assessed the role of nest-site availability in limiting populations of Aphrastura spinicauda (Thorn-Tailed Rayaditos) in Andean temperate rainforests in southern Chile.center dot We conducted an experiment in which nest boxes were added and removed in both forest types during a 5-year period (2008-2013).center dot In old-growth forests compared to second-growth forests, we found 2.3 times higher basal area, 2.4 times higher density of larger trees, and a 2.5 times higher number of small cavities.center dot In second-growth forests, A. spinicauda populations increased by 13% after the nest box addition, and then decreased by 50% after removal, in contrast to no change in old-growth forests.center dot Our findings highlight the importance of maintaining larger trees that provide suitable cavities for this species in second-growth forests. Las poblaciones de aves que nidifican en cavidades están frecuentemente limitadas por el número de cavidades disponibles en bosques de crecimiento secundario. Sin embargo, esta posible limitación de este recurso clave es menos clara en bosques antiguos. Comparamos los atributos del bosque (i.e.,área basal, densidad deárboles grandes, densidad deárboles muertos y densidad de cavidades deárboles) en bosques templados andinos de crecimiento secundario y antiguo del sur de Chile. Para examinar el rol de la disponibilidad de sitios de nidificación en la limitación de poblaciones de Aphrastura spinicauda, monitoreamos sus poblaciones en ambos tipos de bosques durante un periodo de 5 años (2008-2013), mientras realizamos un experimento en el que se agregaron cajas nido y, luego de dos años, se removieron bloqueando la entrada. En los bosques antiguos, en comparación con los bosques de crecimiento secundario, encontramos unárea basal de más del doble (99.6 vs. 43.7 m2 ha-1), una densidad deárboles grandes tres veces mayor (88.2 vs. 36.4árboles ha-1) y un número de cavidades pequeñas 1.5 veces mayor (25.9 vs. 10.3 cavidades ha-1). La densidad de cavidades también aumentó fuertemente con el diámetro de losárboles y elárea basal. En los bosques de crecimiento secundario, A. spinicauda mostró una fuerte respuesta a la adición y subsecuente eliminación de cajas nido, con un aumento en la abundancia poblacional del 13% y luego una disminución del 50%, respectivamente. En contraste, no encontramos impacto en los bosques antiguos. Nuestro experimento enfatiza la importancia de mantenerárboles grandes y muertos en los bosques de crecimiento secundario, degradados y/o manejados. Estosárboles proporcionan cavidades adecuadas para A. spinicauda, y probablemente para muchas otras aves que se reproducen en estas, aumentando sus abundancias en un bosque prioritario para la conservación de biodiversidad a nivel mundial en el cono sur de Sudamérica. Una versión en español de este manuscrito está disponible como material suplementario.
Keywords: aphrastura spinicauda; chile; forest management; resource limitation; secondary cavity-nesting birds; temperate rainforests; thorn-tailed rayadito; bosques templados; limitación de recursos; manejo forestal; nidicadoras secundarias de cavidades